Flipped Classroom sebagai Model Pembelajaran di Era New Normal - Tri Yuli Ardiyansah; Fatimatus Choirunisa (DIDAKTIKA, 2022)
The COVID-19 pandemic has given the effect of changing learning models and requiring teachers to improve their skills in implementing online learning especially in university level. At University of Muhammadiyah Gresik, various learning models were applied by lecturers, one of which was the flipped classroom learning model. Flipped classroom is a learning model in which students are required to study the material first at home or outside the classroom within a few days before the learning process begins. Flipped classroom can make it easier for students to understand the learning material because students have more time study with the explanation videos given. A qualitative approach was used in this study to find out the students’ perception to the implementation of flipped classroom in the learning process. The result of this study found that the implementation of flipped classroom was well received by the students. Students responded that flipped classroom helped them understand the material easier, provided more interactive activities in the classroom, and guided them to improve their learning abilities independently. Thus, flipped classroom was also considered as an innovative learning model that can be implemented the learning process in new normal education.